2020
DOI: 10.4038/jccp.v50i2.7837
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of transient ischaemic attacks

Abstract: TIAs predict stroke risk A transient ischaemic attack (TIA) is not a simple 'mini-stroke', but a major warning sign of an impending stroke that demands urgent attention. About 15-30% of all ischaemic strokes are preceded by TIAs 1-4. The estimated recurrent TIA and stroke risk at three months after a TIA is 17.3% 1 ; the risk of stroke is greatest immediately after a TIA, providing only a short window of opportunity for stroke prevention 2. 52% of all strokes during the first 7 days and 42% of all strokes duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Data from recent studies have confirmed that this indeed is a realistic goal, and have highlighted the importance of emergent evaluation and treatment of TIAs (9,10). This has led to a dramatic change, a virtual paradigm shift, in our approach to the acute management of TIAs, especially over the last two decades (11,12).…”
mentioning
confidence: 98%
“…Data from recent studies have confirmed that this indeed is a realistic goal, and have highlighted the importance of emergent evaluation and treatment of TIAs (9,10). This has led to a dramatic change, a virtual paradigm shift, in our approach to the acute management of TIAs, especially over the last two decades (11,12).…”
mentioning
confidence: 98%